The E3 ligase c-Cbl modulates microglial phenotypes and contributes to Parkinson’s disease pathology - Shumin Deng; Zhiyuan Zhang; Lu Liu; Chen Xu; Di Zhang; Lin Dong; Chunyan Gao; Xiaomin Wang; Zheng Fan (Cell Death Discovery)
Abstract Microglial activation, particularly the polarization between classical (M1 phenotype) and alternative (M2 phenotype) states, plays pivotal roles in the immune pathogenesis of Parkinson’s disease (PD), with the M1 phenotype exerting neurotoxic effects and the M2 phenotype conferring neuroprotection. Modulating microglial polarization toward the M2 phenotype holds therapeutic potential for PD. This study investigated the role of c-Cbl, an E3 ubiquitin ligase implicated in modulating microglial phenotypes and protecting dopaminergic neurons. Our findings revealed that c-Cbl-/- mice exhibited motor deficits, reduced striatal dopamine levels, and progressive dopaminergic neuron loss in the substantia nigra (SN). Genetic ablation of c-Cbl significantly increased proinflammatory cytokine release and microglial activation in the SN, accompanied by a phenotypic shift from M2 to M1 polarization. Furthermore, stereotaxic c-Cbl knockdown in the SN exacerbated behavioral impairments and accelerated dopaminergic neuron degeneration in the MPTP-induced mouse model of PD. At the molecular level, c-Cbl deletion promoted M1 polarization of microglia through dysregulation of the PI3K/Akt signaling pathway, thereby impairing dopaminergic neuronal survival. Collectively, this study demonstrates that c-Cbl knockout recapitulates PD-like pathology and drives microglial activation. Our results establish that c-Cbl orchestrates the transition from neurotoxic M1 to neuroprotective M2 microglial phenotypes, highlighting its central role in PD immunopathogenesis. These findings suggest c-Cbl as a promising therapeutic target for modulating microglial polarization and alleviating PD symptoms.